Thrombocyte Count in Male and Female Adult of Dengue Hemorrhagic Fever Patients - Lelyana Sih Afgriyuspita; Heny Arwati; Hartono Kahar (Universitas Muhammadiyah Surabaya, 2020)
AbstractThe trend of dengue virus infection in Indonesia has changed from children to older groups. Some studies suggested that different gender might affect the different progression of dengue infection, but its mechanism was unclear. This study analyzed the difference by evaluating the daily thrombocyte count pattern. An analytic observational study with a retrospective design was conducted using the secondary data collected from medical records in Dr. Soetomo General Hospital Surabaya during 2017-2018. The samples were adult patients in the age range of 18-55 years old with DHF but without comorbidity or coinfection. The total number of samples was 40 patients. The average of thrombocyte count in both male and female patients decreased since the 3rd day of illness and reached the lowest level on the 6th day of illness then increased on the 7th day but did not reach the normal range. Although the majority of thrombocyte count in females was lower than males, there was no significant difference in thrombocyte count pattern between them. Keyword: Adult, DHF, Thrombocyte, GenderCorrespondence : heny-a@fk.unair.ac.id